EFFECT OF p30 RECOMBINANT PROTEIN ON AFRICAN SWINE FEVER VIRUS IN VITRO REPRODUCTION - Ali Mazloum; I. Yu. Zhukov; A. S. Pershin; A. S. Igolkin; N. N. Vlasova (Ветеринария сегодня)
African swine fever specific prevention means have not been developed yet. However, it is necessary to study the function of definite viral proteins, their role in immune response morphogenesis and induction to determine the components to be included into ASF protection drugs. It was established that p54 and p30 proteins participate in virus penetration and internalization and are able to induce protective antibodies in immunized pigs. The inoculation of these proteins into ASFV-infected cell culture has an impact on virus reproduction to different extents. The results of the study of purified recombinant protein p30 effect, derived from E. coli clone, containing pET32b(+)/р30 plasmid, on ASFV in vitro reproduction are presented. The greatest decrease, including complete inhibition of virus reproduction, was observed when 300 ng of p30 were inoculated into porcine spleen and marrow primary cell cultures, infected with the ASFV Krasnodar 07/17 isolate at the dose of 100 HAU per plate (~ 0.01 HAU per cell). It was noted that if the mixture of p30 and p54 was inoculated into a sample, the virus reproduction was greater compared to the use of only p30.